Descriptive Analysis of CT Scan Findings in Breast Cancer Patients with Bone Metastases in Universitas Andalas Hospital Radiotherapy Installation - Yusriono, Irfan; Tri Septiana, Vina; Rafli, Rhandyka (http://dharmais.co.id/, 2024)
Background: Breast cancer is experiencing the most significant increase in cases among all cancers worldwide. Approximately 65% to 75 % of advanced breast cancer patients will experience bone metastases. CT scan is the most affordable and accessible method for evaluating bone metastases. This study aims to describe the characteristics of CT scan examination of bone metastases in breast cancer patients in the radiotherapy installation at Universitas Andalas Hospital from 2019 until 2021. Methods: A total of 51 patients with breast cancer who had bone metastases were included in this quantitative descriptive study, using a total sampling approach. The clinical data was taken from the medical records at the radiotherapy installation at Andalas University Hospital. The collected data was processed and analyzed using SPSS statistical software. Results: Based on the results, the mean age of patients was 49 years. The most histopathological type was invasive carcinoma mammae of no special type (57%). The most common site for bone metastases is osteo vertebrae (35%). Mixed lesions were the most frequent bone metastatic finding (51%), with fractures occurring in 27% of cases. Conclusions: The results of this study are breast cancer with bone metastases occurring on average at the age of 49 years, histopathological type the most is invasive carcinoma mammae of no special type. Breast cancer with bone metastases is most common in Osteo Vertebrae with mixed lesions as well as pathological fracture with a low percentage.